Shallow Water Seabed Profile Changes in 2016 - 2018 Based on Landsat 8 Satellite Imagery (Case Study: Semak Daun Island, Karya Island and Gosong Balik Layar) - Zahra Safira Aulia; Triguardi Tharik Ahmad; Ratih Rachma Ayustina; Fauzi Tri Hastono; Rizqi Rizaldi Hidayat; Haji Mustakin; Agi Fitrianto; Faras Bagus Rifanditya (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
Seribu Islands is one of the marine tourism destinations in Jakarta. The high level of tourism in the Seribu Islands can be a threat to shallow water seabed profile habitat. Therefore, monitoring of changes in shallow water seabed profile habitat is needed so the sustainability can be monitored. This study aimed to determine changes in the shallow water seabed profile on Karya Island, Semak Daun Island, and Gosong Balik Layar in 2016 and 2018 based on Landsat 8 Satellite Imagery. Methods of this research used satellite image pre-processing, image classification, field survey, image reclassification, and accuracy assessment. The results showed that the coral area had decrease trend, while the area of Seagrass mix Seaweed had increased. The result of this classification had an accuracy value of 71.52%. Keywords: remote sensing, multispectral imagery, Lyzenga, benthic habitat, Seribu Island